2022
DOI: 10.1038/s41398-022-02172-w
|View full text |Cite
|
Sign up to set email alerts
|

Shared brain and genetic architectures between mental health and physical activity

Abstract: Physical activity is correlated with, and effectively treats various forms of psychopathology. However, whether biological correlates of physical activity and psychopathology are shared remains unclear. Here, we examined the extent to which the neural and genetic architecture of physical activity and mental health are shared. Using data from the UK Biobank (N = 6389), we applied canonical correlation analysis to estimate associations between the amplitude and connectivity strength of subnetworks of three major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 97 publications
(112 reference statements)
1
4
0
Order By: Relevance
“…However, some scholars have found that the effects of different exercise intensities on people’s subjective well-being vary, and in particular, moderate-intensity physical activity has the best effect on people’s subjective well-being [ 17 ]. Moreover, evidence that physical activity affects people’s subjective well-being can be inferred from genetic and cognitive neuroscience studies, but the physiological mechanisms need to be further clarified [ 18 ]. In summary, Hypothesis 1 is proposed: physical activity positively affects university students’ subjective well-being.…”
Section: Introductionmentioning
confidence: 99%
“…However, some scholars have found that the effects of different exercise intensities on people’s subjective well-being vary, and in particular, moderate-intensity physical activity has the best effect on people’s subjective well-being [ 17 ]. Moreover, evidence that physical activity affects people’s subjective well-being can be inferred from genetic and cognitive neuroscience studies, but the physiological mechanisms need to be further clarified [ 18 ]. In summary, Hypothesis 1 is proposed: physical activity positively affects university students’ subjective well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a family history of mental health issues consistently exhibited negative loadings, particularly within the first CCA component for sMRI (e.g., maternal nervous breakdown, paternal employment or legal troubles), dMRI streamline count (e.g., parental employment/legal troubles, alcohol use, depression), and SST fMRI (e.g., parental employment/legal troubles). These bivariate associations between behavior, genetic liability, and the brain have been previously reported[65][66][67][68][69] . Building on this foundation, our findings show the novel tripartite associations among genetics, brain IDPs, and behaviors, suggesting a gene-brain-behavior pathway.In predicting cognitive outcomes, multivariate patterns of GPSs trained with machine learning showed moderate to good performance.…”
supporting
confidence: 55%
“…A similar argumentation is valid with respect to chronic physical activity, where it is also plausible that people with a higher creative potential habitually walk more often and for longer periods of time. It should also be mentioned that other, hidden variables (like genes or brain architecture) could exert an influence on both physical activity and creativity (see, e.g., Zhang et al, 2022, for mental health). However, available experimental studies clearly argue for the enhancing effect of acute and chronic physical activity (Rominger, Schneider, et al, 2022), and the present study adds to these observations.…”
Section: Discussionmentioning
confidence: 99%